2019
DOI: 10.3389/fimmu.2019.02958
|View full text |Cite
|
Sign up to set email alerts
|

The CD40-ATP-P2X7 Receptor Pathway: Cell to Cell Cross-Talk to Promote Inflammation and Programmed Cell Death of Endothelial Cells

Abstract: Extracellular adenosine 5 ′-triphosphate (ATP) functions not only as a neurotransmitter but is also released by non-excitable cells and mediates cell-cell communication involving glia. In pathological conditions, extracellular ATP released by astrocytes may act as a "danger" signal that activates microglia and promotes neuroinflammation. This review summarizes in vitro and in vivo studies that identified CD40 as a novel trigger of ATP release and purinergic-induced inflammation. The use of transgenic mice with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 95 publications
(172 reference statements)
0
21
0
Order By: Relevance
“…The extracellular release of ATP induces the expression of MMP9 and IL-1β in injured brain tissue [ 15 ]. These inflammatory molecules promote the disruption of BBB through the degradation of tight junction proteins and endothelial cell death [ 16 ]. BBB disruption promotes the infiltration of circulating immune cells in the injured brain.…”
Section: Introductionmentioning
confidence: 99%
“…The extracellular release of ATP induces the expression of MMP9 and IL-1β in injured brain tissue [ 15 ]. These inflammatory molecules promote the disruption of BBB through the degradation of tight junction proteins and endothelial cell death [ 16 ]. BBB disruption promotes the infiltration of circulating immune cells in the injured brain.…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, these studies could be applied to other nucleotide receptors. Ionotropic P2X and metabotropic P2Y nucleotide receptors are involved in mechanotransduction in different tissues in physiological conditions or after injury or inflammatory processes [ 32 , 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our proteomic analysis revealed significantly higher abundance of the costimulatory molecule CD40 in pRMG after stimulation with IFNγ. Intriguingly, CD40 has been shown to play a vital role in DR pathogenesis (123)(124)(125). A study with transgenic mice, which express CD40 only in Müller cells, demonstrated that the upregulation of CD40 in Müller cells under diabetic conditions is sufficient for thriving leukostasis and degeneration of capillaries, thus promoting retinal inflammation and neurodegeneration in streptozotocin induced DR (124).…”
Section: Discussionmentioning
confidence: 99%